Kontekstualisasi Surat An-Nisa (4:3) Perspektif Tafsir Ibnu Abbas dan Tafsir Al-Misbah Karya Quraish Syihab di Era Kontemporer - Saniatin, Any; Mubarok, Imam Anas; Awan, Edi (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This study discusses the explanation of Surah An-Nisa (4):3 according to the tafsir of Ibn Abbas and the interpretation of the misbah written by the Quraish syihab related to polygamy. Polygamy is a marriage that has many partners. Surah An-Nisa (4):3 explains that a man may marry more than one woman under certain conditions. Related to this, there are many pros and cons among the community because it is considered deviant behavior. This study uses a normative research method, namely by using library research data and then analyzed using descriptive comparative analysis, namely comparing the interpretation of Ibn Abbas M. Quraish Shihab in the tafsir of Al-Misbah to Surah An-Nisa' (4):3, then comparing by looking for differences and similarities between interpreters in explaining the verses of the Qur'an. So it can be concluded that in the tafsir Ibn Abbas allows polygamy on the condition that it must be fair, because during the spread of Islam many companions died and forbade more than four, while in the tafsir misbah by M. Quraish Shihab stated that polygamy does not only look in terms of fairness but must look in terms of the conditions experienced to be able to do polygamy.